2017
DOI: 10.1016/j.envres.2017.03.057
|View full text |Cite
|
Sign up to set email alerts
|

Impact of community disadvantage and air pollution burden on geographic disparities of ovarian cancer survival in California

Abstract: Ovarian cancer survival varies geographically throughout California. The objective of this study is to determine the impact of living in disadvantaged communities on spatial patterns of survival disparities. Including a bivariate spatial smooth of geographic location within the Cox proportional hazard models is an effective approach for spatial analyses of cancer survival. Women diagnosed with advanced Stage IIIC/IV epithelial ovarian cancer (1996–2006) were identified from the California Cancer Registry. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…CalEnviroScreen is noteworthy in this regard. Researchers used CalEnviroScreen to model ovarian cancer survival rates [ 44 ], predict spatial patterns in disease burden [ 45 ], evaluate electrical grid siting alternatives [ 46 ], and corroborate environmental racism and cumulative impact claims by community members opposing the siting of a new hazardous waste facility in their community [ 47 ]. In addition, CalEnviroScreen is the only screening tool among these four with statewide coverage, and it is meant to assist the State of California in locating the most environmentally burdened, “disadvantaged communities,” for the targeted receipt of a quarter of the Greenhouse Gas Reduction Funds obtained through California’s carbon cap-and-trade program [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…CalEnviroScreen is noteworthy in this regard. Researchers used CalEnviroScreen to model ovarian cancer survival rates [ 44 ], predict spatial patterns in disease burden [ 45 ], evaluate electrical grid siting alternatives [ 46 ], and corroborate environmental racism and cumulative impact claims by community members opposing the siting of a new hazardous waste facility in their community [ 47 ]. In addition, CalEnviroScreen is the only screening tool among these four with statewide coverage, and it is meant to assist the State of California in locating the most environmentally burdened, “disadvantaged communities,” for the targeted receipt of a quarter of the Greenhouse Gas Reduction Funds obtained through California’s carbon cap-and-trade program [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been relatively little particulate contamination in the U.S. [ 27 ]. Thus, research in this area has been relatively scarce and the current studies mainly focus on areas where PM pollution continues to be relatively high, such as California [ 28 ] and Arizona [ 29 ]. However, as these studies were mainly concentrated in megacities, the results are fragmented and it is difficult to understand these trends from a macroscopic perspective.…”
Section: Introductionmentioning
confidence: 99%
“…This was similar to Gaffron and Niemeier [ 19 ], who observed a very low bivariate strength of association (R 2 = 0.018) between PM 2.5 (environmental variable) and emergency visits for asthma (health outcome) employing CalEnviroScreen census tract data in six Sacramento, CA region counties. Especially, studies are needed combining longitudinal data sets of disease occurrence with CalEnviroScreen and other hazard measures [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies at similar spatial scales and resolutions have established relationships of environmental hazards and disease risk with race and socioeconomic status, with implications for resource allocation and policy [ 14 , 15 , 19 , 24 , 60 ]. Prior studies have also shown geographic indicators of socioeconomic status or vulnerability to be associated with hospitalization rates or disease occurrence [ 2 , 30 ]. However, few studies explicitly evaluate and describe the multiple patterns of association that occur across a range of health hazards and vulnerabilities at the census-tract scale [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation